Epitaxial growth of high-quality GaN with a high growth rate at low temperatures by radical-enhanced metalorganic chemical vapor deposition - Arun Kumar Dhasiyan; Frank Wilson Amalraj; Swathy Jayaprasad; Naohiro Shimizu; Osamu Oda; Kenji Ishikawa; Masaru Hori (Scientific Reports)
Abstract Using our recently developed radical-enhanced metalorganic chemical vapor deposition (REMOCVD) technique, we have grown gallium nitride (GaN) on bulk GaN and GaN on Si templates. Three features make up this system: (1) applying very high-frequency power (60 MHz) to increase the plasma density; (2) introducing H2 and N2 gas in the plasma discharge region to produce active NHx radical species in addition to nitrogen radicals; and (3) supplying radicals under remote plasma arrangement with a Faraday cage to suppress charged ions and photons. Using this new REMOCVD system, it was found that high-quality crystals can be grown at lower temperatures than that of MOCVD but the disadvantage was that the growth rate was smaller as 0.2–0.8 μm/h than that by MOCVD. In the present work, we have used a pBN inner shield to prevent the deactivation of radicals to increase the growth rate. The growth conditions such as the plasma power, trimethylgallium (TMG) source flow rate, N2 + H2 gas mixture flow rate, and the ratio of N2/H2 were optimized and it was found that the growth rate could be increased up to 3.4 μm/h with remarkably high crystalline quality comparable to that of MOCVD. The XRD-FWHM of GaN grown on the GaN/Si template and the bulk GaN substrate were 977 arcsec and 72 arcsec respectively. This work may be very promising to achieve high-power GaN/GaN devices.